A COMPARATIVE STUDY TO EVALUATE THE POSITIVE PREDICTIVE VALUE OF BIOCHEMICAL MARKERS WITH CLINICAL RIPASA SCORE IN ACUTE APPENDICITIS: AN IN VIVO STUDY - Singh, Harpinder; Johri, Vishwas; Saran, Tejpal Singh (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: We evaluated the positive predictive value of biochemical markers with clinical Raja Isteri Pengiran Anak Saleha Appendicitis (RIPASA) score and the sensitivity and diagnostic accuracy. Methods: 75 patients who presented to the Emergency/General Surgery Department of Pacific Medical College and Hospital, Udaipur, with right iliac fossa (RIF) pain and who were suspected of acute appendicitis. A detailed history, clinical examination, and laboratory investigations were done which included a routine RIPASA score calculated. Results: RIF pain was present in all the patients, followed by vomiting (98.67%), and fever in 92%. Twenty-one patients had raised white blood cell (WBC) counts, out of them 15 patients had both raised WBC counts and raised C-reactive protein (CRP) and 6 had normal CRP. 52 patients had raised CRP levels, out of them 15 patients had both raised WBC counts and raised CRP and 37 had normal WBC counts. 17 patients had both CRP and WBC counts in normal range, but were diagnosed to have appendicitis according to RIPASA score. Our results show that raised CRP and WBC counts had a sensitivity of 28.85% and specificity of 73.91% with a diagnostic accuracy of 42.67%. Conclusion: When combined with WBC, CRP has good discriminatory power for appendicitis despite its inability to reliably predict acute appendicitis when used alone. However, a cutoff point for CRP that predicted perforated appendicitis could not be determined.